Service Users as Collaborators in Social Work Practice, Research, and Education - Cabiati, Elena; Panciroli, Chiara (Socialinė teorija, empirija, politika ir praktika, 2019)
The idea that social work needs to be concerned with thinking and acting in a more collaborative way with the people in need is common around the world. At the international level, codes of ethics and social work principles inspire practitioners, researchers, and educators in bridging the gap between themselves and people in trouble, commonly known as service users. Beyond a common agreement around such principle, to realize collaborative relationships in practice is a challenge that requires prudence, coherence, and methodology. The Relational social work method supports the practical development of participation, collaboration, and reciprocity. Through concepts and examples, this article aims to describe how service users can assume the role of collaborators in social practice, research, and education.